Adolescent attachment to parents and peers in singletons and twins born with assisted and natural conception. Issue 2 (8th March 2022) - Flykt, M S; Prince, M; Vänskä, M; Lindblom, J; Minkkinen, J; Tiitinen, A; Poikkeus, P; Biringen, Z; Punamäki, R -L
Abstract: STUDY QUESTION: Does adolescent attachment to parents and peers differ between singletons and twins born with ART or natural conception (NC)? SUMMARY ANSWER: Adolescent attachment anxiety with the father was higher among NC singletons than among ART and NC twins, whereas attachment avoidance with the father was higher in ART singletons than in NC singletons and NC twins. No differences were found in attachment to the mother, best friend or romantic partner. WHAT IS KNOWN ALREADY: Most studies have not found differences between ART and NC singletons in parent–adolescent relationships, but twin relationships may be more at risk. No previous study has examined all four groups in the same study, or specifically looked at attachment relationships. STUDY DESIGN, SIZE, DURATION: This was an 18-year, prospective and controlled longitudinal study with families of 496 ART singletons, 101 ART twin pairs, 476 NC singletons and 22 NC twin pairs. Families were recruited during the second trimester of pregnancy; the ART group was recruited from five infertility clinics in Finland and the control group was recruited from a hospital outpatient clinic during a routine visit. PARTICIPANTS/MATERIALS, SETTING, METHODS: Mothers and fathers gave background information for this study during pregnancy, and during the child's first year and early school age (7–8 years). For the ART group, infertility characteristics and prenatal medical information was also obtained from the patient registry of the infertility clinics. Children (originally 50% girls) filled in electronic questionnaires related to their attachment to mother, father, best friend and romantic partner ( Experiences in Close Relationships—Relationship Structures ) at 17–19 years of age. MAIN RESULTS AND THE ROLE OF CHANCE: Adolescent attachment anxiety to father was higher in NC singletons than in ART twins, P  = 0.004 and marginally higher than in NC twins, P  = 0.06. Adolescent attachment avoidance to father was higher in ART singletons than in NC singletons, P  = 0.006 and marginally higher than in NC twins, P  = 0.055. LIMITATIONS, REASONS FOR CAUTION: The sample size was small especially in the NC twin group and there was drop-out over the 18-year time period, especially among boys and families with lower parental education level. The study only included native Finnish-speaking families. The results could differ in a more diverse population. ART singletons were younger and had fewer siblings than ART twins and NC children, and ART and NC twins had more newborn health risks than ART and NC singletons. WIDER IMPLICATIONS OF THE FINDINGS: The study adds to a growing body of evidence that neither ART treatments nor being a twin places mother–child relationships or peer relationships at long-term risk. However, in our study, which was the first to examine both ART and twinhood simultaneously, we found that there may be more problems in father–adolescent relationships, but only in ART singletons and only related to attachment avoidance. Our findings suggest that men, as well as women, should receive enough support in pre- and peri-natal health care during and after infertility treatments. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by Academy of Finland (grant number 2501308988), the Juho Vainio Foundation and the Finnish Cultural Foundation. The authors report no conflict of interest. TRIAL REGISTRATION NUMBER: N/A.